Educational Interpretation of Verses on Religious Moderation and Their Relevance in the Contemporary World of Education - Rahmawati Eka Nurhidayah; Choirul Anam (LP3M Pascasarjana STAI Ibnurusyd, 2025)
Religious moderation has become a crucial discourse in responding to the challenges of extremism, intolerance, and polarization in contemporary societies, particularly within the educational sphere. This study aims to analyze the educational interpretation of Qur’anic verses related to religious moderation and to examine their relevance in the context of modern education. Employing a qualitative library research method, the study uses a thematic (maudhu‘i) approach to interpret selected Qur’anic verses that emphasize balance (wasatiyyah), justice (‘adl), tolerance (tasamuh), and inclusivity in human relations. The findings indicate that Qur’anic teachings on moderation are not merely theological concepts but possess strong pedagogical implications, including the development of holistic curricula, dialogical learning models, and value-based character education. In the contemporary educational context, these values are relevant for fostering critical thinking, mutual respect, social harmony, and ethical responsibility among learners in multicultural and pluralistic environments. The study concludes that integrating the educational interpretation of moderation-oriented Qur’anic verses into educational practices can contribute significantly to building inclusive, peaceful, and transformative educational systems. This research offers a conceptual framework for educators and policymakers to embed religious moderation as a foundational value in contemporary education.